2013
DOI: 10.1007/s12665-012-2203-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil radon in winter months under snowpack in Hokkaido, Japan

Abstract: Soil radon (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Energy and efficiency calibrations were periodically carried out, as well as checking the background. Details of the measurements were described in Fujiyoshi et al (2010Fujiyoshi et al ( , 2013.…”
Section: Gamma Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Energy and efficiency calibrations were periodically carried out, as well as checking the background. Details of the measurements were described in Fujiyoshi et al (2010Fujiyoshi et al ( , 2013.…”
Section: Gamma Spectrometrymentioning
confidence: 99%
“…Another important and basic aspect exists in the study of 222 Rn in soil air to elucidate mechanisms of its migration in soil and transportation to the ground surface (Nazaroff 1992;Neznal and Neznal 2005;Fujiyoshi et al 2010Fujiyoshi et al , 2013. Soil radon monitoring has shown that 222 Rn activity concentration varies to a great extent depending on geological, meteorological and hydrological factors, and that its migration through the soil and rock is controlled not only by diffusion but convection It is widely recognized that both liquid and gaseous water movements are fundamental factors controlling many processes in soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aims at evaluating 40 K isotopic composition 96 ( 40 K/K) in forest soils under different environmental con-97 ditions in Tomakomai (Hokkaido, Japan) and in Slovenia 98 with non-destructive techniques of gamma spectrometry 99 and of energy-dispersive X-ray fluorescence spectrometry 100 (EDXRF), and at elucidating possible reasons for its 101 inhomogeneous distribution in soil, and hopefully propos-102 ing 40 0 N, 27 km 2 in total area) was shown in our previous 109 paper [12]. Annual mean temperature and precipitation in 110 the site are 6.4°C and 1,450 mm, respectively.…”
mentioning
confidence: 91%